Service Network Design of Bike Sharing Systems Analysis and Optimization - Vogel, Patrick; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This monograph presents a tactical planning approach for service network design in metropolitan areas. Designing the service network requires the suitable aggregation of demand data as well as the anticipation of operational relocation decisions. To this end, an integrated approach of data analysis and mathematical optimization is introduced. The book also includes a case study based on real-world data to demonstrate the benefit of the proposed service network design approach. The target audience comprises primarily research experts in the field of traffic engineering, but the book may also be beneficial for graduate students.
Introduction -- Bike sharing in the context of urban mobility -- Service network design as a logistical challenge in the reliable provision of service in bike sharing systems -- Determination of typical bike flows -- Case study: Generation of typical bike flows for Citybike Wien -- Service network design of bike sharing systems -- Case study: Service network design of Citybike Wien -- Conclusions and outlook.
Keywords: Transportation engineering; Traffic engineering; Operations research; Management science; Technological innovations; Dynamics; Nonlinear theories; Transportation Technology and Traffic Engineering; Operations Research, Management Science; Innovation and Technology Management; Applied Dynamical Systems